Normalized Differential Power Analysis - for ghost peaks mitigation - Chen, Juncheng (2021)
The attack efficacy of Differential Power Analysis (DPA), a popular side channel evaluation technique for key extraction, is compromised by the false highest Difference Of Means (DOMs) value (‘ghost peaks’) in the DOMs matrix produced in a conventional DPA. The ghost peak is generated by the wrong key guess and always occurs in the conventional DPA when the number of side channel traces is not enough. In this paper, an improved version of the conventional DPA termed as Normalized DPA (NDPA) is proposed to circumvent the ghost peak. With the analysis on the generation of ghost peaks in the conventional DPA, we observed that by normalizing the DOMs matrix, the ghost peaks can be greatly suppressed. We model the proposed NDPA mathematically and show that it performs better than the conventional DPA. We further provide the experimental validations on a set of 200k power simulation traces on AES SBox and 500 EM traces from ASCAD dataset. Based on the attack results of these datasets, our proposed NDPA requires (up to 68%) lesser number of traces to reveal a correct key when compared to the conventional DPA.